2021
DOI: 10.1088/1755-1315/848/1/012049
|View full text |Cite
|
Sign up to set email alerts
|

About the use of plant-based complex of alfalfa in production of dairy products

Abstract: Fermented milk products perform a special role in rational human nutrition and is an important factor in treatment and prevention of various diseases of gastrointestinal tract. Today, close attention is paid to development and inclusion of various herbal components in production technologies of fermented dairy products. The article discusses the issue of using the plant complex of alfalfa in production technology of fermented dairy products. Alfalfa contains many useful substances that are so necessary for a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…It is found that biologically active substances in plants can positively influence the growth parameters of probiotics due to the multicomponent nature of food sources [15]. For instance, various plant raw materials such as topinambur, licorice, burdock, and alfalfa have been incorporated into fermented milk products to stimulate the growth of lactic acid microorganisms [16][17][18][19][20]. However, despite these findings, unresolved questions persist regarding the application of these plant-based ingredients in dairy products.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…It is found that biologically active substances in plants can positively influence the growth parameters of probiotics due to the multicomponent nature of food sources [15]. For instance, various plant raw materials such as topinambur, licorice, burdock, and alfalfa have been incorporated into fermented milk products to stimulate the growth of lactic acid microorganisms [16][17][18][19][20]. However, despite these findings, unresolved questions persist regarding the application of these plant-based ingredients in dairy products.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Furthermore, the paper [18] investigates the use of alfalfa in dairy production, emphasizing its potential to improve product quality and nutritional properties. This study highlights the broader potential of plant-based ingredients in enhancing dairy nutrition and fostering innovation in the industry.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…M. varia contains omega-3 fatty acids, which are necessary to improve milk quality and increase meat production in ruminants [15]. The plant complex of alfalfa, which contains substances necessary for humans (especially in unfavorable environmental conditions), is used in technology for the production of fermented milk products [16]. It is also worth noting the insecticidal and fungicidal potential of the use of saponins identified in Medicago.…”
Section: Introductionmentioning
confidence: 99%